gamma-band deficiency and abnormal thalamocortical activity in P/Q-type channel mutant mice - Llinas, Rodolfo R.; Choi, Soonwook; Urbano, Francisco J.; Shin, Hee-Sup (NATL ACAD SCIENCES, 2007)
Thalamocortical in vivo and in vitro function was studied in mice lacking P/Q-type calcium channels (Ca(v)2.1), in which N-type calcium channels (Ca(v)2.2) supported central synaptic transmission. Unexpectedly, in vitro patch recordings from thalamic neurons demonstrated no gamma-band subthreshold oscillation, and voltage-sensitive dye imaging demonstrated an absence of cortical gamma-band-dependent columnar activation involving cortical inhibitory interneuron activity. In vivo electroencephalogram recordings showed persistent absence status and a dramatic reduction of gamma-band activity. Pharmacological block of T-type calcium channels (Ca(v)3), although not noticeably affecting normal control animals, left the knockout mice in a coma-like state. Hence, although N-type calcium channels can rescue P/Q-dependent synaptic transmission, P/Q calcium channels are essential in the generation of gamma-band activity and resultant cognitive function.
Keywords: VOLTAGE-ACTIVATED CURRENTS; CENTRAL-NERVOUS-SYSTEM; CALCIUM-CHANNEL; CA2+ CHANNELS; SYNAPTIC-TRANSMISSION; NEUROTRANSMITTER RELEASE; TRANSMITTER RELEASE; NEURONS; MOUSE; FREQUENCY